Why Does Fdi Go Where it Goes? : New Evidence From the Transition Economies - Kinoshita, Yuko (IMF Working Papers; Working Paper ;, 2003)
This paper examines the importance of agglomeration economies and institutions vis-a-vis initial conditions and factor endowments in explaining the locational choice of foreign investors. Using a unique panel data set for 25 transition economies between 1990 and 1998, we find that the main determinants are institutions, agglomeration, and trade openness. We find important differences between the Eastern European and Baltic countries, on the one hand, and the CIS countries on the other: in the latter group, natural resources and infrastructure matter, while agglomeration matters only for the former group.